2021
DOI: 10.1590/1516-4446-2020-1577
|View full text |Cite
|
Sign up to set email alerts
|

Translating science into policy: mental health challenges during the COVID-19 pandemic

Abstract: Several stressors associated with the coronavirus disease 2019 (COVID-19) are expected to affect the mental health of global populations: the effects of physical distancing, quarantine, and social isolation; the emotional suffering of health and other frontline workers; neuropsychiatric sequelae in those affected by the virus; the impact to families of lives lost to the disease; differential effects for those with severe mental disorders; and the consequences of social and economic deterioration. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 73 publications
0
13
0
5
Order By: Relevance
“…The findings of this study showed adolescents from disadvantaged families are more likely to have emotional problems, probably due to uncertainty and anxiety among adolescents regarding their families' financial difficulties [44]. The negative emotional consequences indicate the need to intensify mental health protection actions, giving priority to the most vulnerable families [43].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The findings of this study showed adolescents from disadvantaged families are more likely to have emotional problems, probably due to uncertainty and anxiety among adolescents regarding their families' financial difficulties [44]. The negative emotional consequences indicate the need to intensify mental health protection actions, giving priority to the most vulnerable families [43].…”
Section: Discussionmentioning
confidence: 71%
“…During the period of social restraint measures, low-income families had more difficulties in facing the pandemic [40]. In Brazil, there was a greater reduction in family income among the poorest sections of the population, while informal workers were left without work, raising concerns about family maintenance and food insecurity [41][42][43]. The findings of this study showed adolescents from disadvantaged families are more likely to have emotional problems, probably due to uncertainty and anxiety among adolescents regarding their families' financial difficulties [44].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, people with this diagnosis during a pandemic should have received more care and attention. Unfortunately, it did not happen—patients had difficulty getting in touch with a doctor let alone accessing better care and prevention [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Global consensus and national policies have emphasized deinstitutionalization, or a shift in providing mental health care from institutional to community settings. The integration of psychiatry with somatic medicine and the development of a community psychiatry requires the organization and creation of a complex and coordinated care system, including primary care, specialized mental health care, crisis management services, housing programs, inpatient units, and centers running a specialized treatment program and supervising this system and consulting them clinical academic centers [ 11 ]. This creates great opportunities to introduce innovative technologies in the form of telemedicine systems coordinating the operation of a multi-module care system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation